2014
DOI: 10.1212/wnl.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Electrographic status epilepticus and long-term outcome in critically ill children

Abstract: Among children with acute neurologic disorders who were reported to be neurodevelopmentally normal before PICU admission, ESE but not ES was associated with an increased risk of unfavorable global outcome, lower health-related quality of life scores, and an increased risk of subsequently diagnosed epilepsy even after adjusting for neurologic disorder category, EEG background category, and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 38 publications
4
143
0
Order By: Relevance
“…Both HPDs and HVSWs may occur at such high frequency in mice (Table 1) that they might be considered as electrographic SE (ESE), as, for instance, occurring in children with acute neurologic disorders and contributing to secondary brain injury and worse short‐term and long‐term outcomes 54. In patients, ESE is defined as either a single 30‐min electrographic seizure or a series of recurrent independent electrographic seizures totaling more than 30 min in any 1‐h period (50% seizure burden) 54.…”
Section: Discussionmentioning
confidence: 99%
“…Both HPDs and HVSWs may occur at such high frequency in mice (Table 1) that they might be considered as electrographic SE (ESE), as, for instance, occurring in children with acute neurologic disorders and contributing to secondary brain injury and worse short‐term and long‐term outcomes 54. In patients, ESE is defined as either a single 30‐min electrographic seizure or a series of recurrent independent electrographic seizures totaling more than 30 min in any 1‐h period (50% seizure burden) 54.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to short seizures, convulsive or electrographic‐only SE45 has a negative impact on the long‐term QoL 5. However, population‐based studies comparing adults with childhood‐onset epilepsy with or without SE showed no association with educational attainment, employment status, and income 33.…”
Section: Long‐term Outcomes Of Sementioning
confidence: 99%
“…Long‐term mortality data after an episode of SE, including in‐hospital deaths, is 0%‐22% in children5, 6, 17, 26, 27, 28, 29, 33, 34, 35, 37, 38, 45, 53 and 0%‐57% in adults 10, 11, 12, 17, 19, 20, 43, 54…”
Section: Long‐term Outcomes Of Sementioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by an enduring predisposition to generate spontaneous seizures often associated with cognitive and psychiatric comorbidities with negative social consequences. One major clinical need in epilepsy is to identify antiepileptogenesis treatments for preventing or arresting the development of the disease in patients who have been exposed to potentially epileptogenic brain insults, including status epilepticus (SE) (Holtkamp et al, 2005;Wagenman et al, 2014). The development of such treatments has been hampered by the lack of non-invasive biomarkers that could be used to identify the patients at-risk, thereby allowing to design affordable clinical studies (Engel et al, 2013;Pitkanen and Engel, 2014).…”
Section: Introductionmentioning
confidence: 99%